Stability of the Manual Ability Classification System in young children with cerebral palsy. (10th January 2019) - Burgess, Andrea; Boyd, Roslyn; Ziviani, Jenny; Chatfield, Mark D; Ware, Robert S; Sakzewski, Leanne
Abstract : Aim: To examine the stability over time of the Manual Ability Classification System (MACS) levels in children with cerebral palsy (CP) aged 18 to 60 months. Method: This was a prospective longitudinal population‐based study of 252 Australian children (160 males [63%] 92 females [37%]; mean age [SD] 41.7mo [14], range 17.2mo–69.2mo) with CP. Children were classified at 18 months ( n =70), 24 months ( n =131), 30 months ( n =173), 36 months ( n =209), 48 months ( n =226), and 60 months ( n =221) of age. Stability of the MACS was examined using the proportion of specific positive agreement and transition proportions, which are measures of agreement. Results: There were 1030 unique observations, with each of the 252 participants seen between two and six occasions (median=4). Average specific positive agreement over the study period was 76% for MACS level I, 67% for level II, 50% for level III, 51% for level IV, and 83% for level V. MACS levels I and V have the highest degree of stability, while levels III and IV have the lowest. We show how this may be explained by the proportion of children in each MACS level. Interpretation: Using measures of agreement rather than measures of reliability provides accurate information when measuring stability over time of an ordinal classification system. The relative stability of MACS levels can be explained by the proportion of children in each level. What this paper adds: Children classified in Manual Ability Classification System (MACS) levels III and IV change levels at next assessment about 50% of the time. Children should be assessed with the MACS regularly, particularly those in levels III and IV. Stability within ordinal classification level categories can be predicted using a measurement error model. Transition proportions or specific agreement is recommended for reporting stability of ordinal classification systems. What this paper adds: Children classified in Manual Ability Classification System (MACS) levels III and IV change levels at next assessment about 50% of the time. Children should be assessed with the MACS regularly, particularly those in levels III and IV. Stability within ordinal classification level categories can be predicted using a measurement error model. Transition proportions or specific agreement is recommended for reporting stability of ordinal classification systems. This article is commented on by Hanna on page 740 of this issue. This article's abstract has been translated into Spanish and Portuguese. Follow the links from the abstract to view the translations. Resumo: Estabilidade do Sistema de Classificação da Habilidade Manual (MACS) em crianças jovens com paralisia cerebral Objetivo: Examinar a estabilidade ao longo do tempo dos níveis do Sistema de Classificação da Habilidade Manual (MACS) em crianças com paralisia cerebral (PC) com idade entre 18 e 60 meses. Método: Este foi um estudo prospectivo de caráter longitudinal, com amostra baseada no estudo da população de 252 crianças Australianas (160 meninos [63%], 92 meninas [37%]; idade média [desvio padrão] de 41, 7 meses [14], variação de 17, 2 a 69, 2 meses de idade]) com PC. As crianças foram classificadas aos 18 meses ( n  = 70), 24 meses ( n  = 131), 30 meses ( n  = 173), 36 meses ( n  = 209), 48 meses ( n  = 226), e aos 60 meses ( n  = 221) de idade. A estabilidade do MACS foi examinada utilizando a proporção de concordância positiva específica e proporções de transição, sendo estas as medidas de concordância. Resultados: Foram realizadas um total de 1.030 observações com os 252 participantes, os quais foram avaliados individualmente entre dois e seis momentos (média = 4). A média de concordância específica positiva durante o estudo foi de 76% para MACS nível I, 67% para nível II, 50% para nível III, 51% para nível IV, e 83% para nível V. Os classificados com MACS nível I e V tiveram os maiores graus de estabilidade, enquanto os classificados com os níveis III e IV tiveram os menores graus de estabilidade. Estes resultados podem ser explicados pela proporção de crianças classificadas em cada nível do MACS. Interpretação: A utilização de medidas de concordância ao invés de medidas de confiabilidade proporciona informações mais precisas quando se mensura estabilidade ao longo do tempo com um sistema de classificação ordinal. A estabilidade relativa dos níveis do MACS pode ser explicada pela proporção de crianças classificadas em cada nível. Resumen: Estabilidad del Sistema de Clasificación de Habilidad Manual (MACS) en niños pequeños con parálisis cerebral Objetivo: Examinar la estabilidad en el tiempo de los niveles del Sistema de Clasificación de Habilidad Manual (MACS) en niños con parálisis cerebral (PC) de 18 a 60 meses. Método: Este fue un estudio prospectivo longitudinal basado en la población de 252 niños australianos (160 [63%] hombres, 92 mujeres [37%]; edad media [DE] 41.7mo [14], rango 17.2mo–69.2mo]) con PC. Los niños se clasificaron a los 18 meses (n = 70), 24 meses (n = 131), 30 meses (n = 173), 36 meses (n = 209), 48 meses (n = 226) y 60 meses (n = 221) de edad. La estabilidad del MACS se examinó utilizando la proporción de acuerdo positivo específico y las proporciones de transición, que son medidas de acuerdo. Resultados: Con cada uno de los 252 participantes vistos entre dos y seis ocasiones (mediana = 4) hubo 1030 observaciones únicas. La concordancia positiva específica promedio durante el período de estudio fue de 76% para MACS nivel I, 67% para nivel II, 50% para nivel III, 51% para nivel IV y 83% para nivel V. Los niveles I y V de MACS son los más altos de estabilidad, mientras que los niveles III y IV tienen los más bajos. Mostramos cómo esto puede explicarse por la proporción de niños en cada nivel de MACS. Interpretación: El uso de medidas de acuerdo ‐ en lugar de medidas de confiabilidad ‐ proporciona información precisa cuando se mide la estabilidad en el tiempo de un sistema de clasificación ordinal. La estabilidad relativa de los niveles de MACS puede explicarse por la proporción de niños en cada nivel.